Pola Penggunaan Antibiotik pada Penyakit ISPA di Puskesmas Koto Baru Kota Sungai Penuh Periode 2022-2023 - Zhafirah, Wara; Andriani, Medi; Sanuddin, Mukhlis (Jurnal Akademika Baiturrahim Jambi, 2025)
Acute Respiratory Infections (ARI) are among the most common diseases in the community and often require the use of antibiotics for treatment. However, inappropriate use of antibiotics can lead to antibiotic resistance, which is a global health problem. This study aims to analyze the patterns of antibiotic use in ARI patients at Koto Baru Health Center, Sungai Penuh City, during the period 2022-2023. This research is a descriptive study with a retrospective approach. Data were collected from the medical records of patients diagnosed with ARI at Koto Baru Health Center during the period 2022-2023. The information collected included the type of antibiotic used, route of administration, frequency of administration, and rationality. The data were analyzed to identify patterns of antibiotic use and their compliance with existing therapeutic guidelines. The study found that, based on gender, 72% of the patients were female. Based on age, 52% of the patients were 13-33 years old and 68% were 33-53 years old. A total of 87% of the patients did not have any comorbidities. The most commonly used antibiotic was amoxicillin, with 100% appropriate route of administration. The frequency of appropriate antibiotic administration was 84% in patients aged 13-33 years and 91% in patients aged 33-53 years. The rationality of antibiotic use was recorded at 85% in patients aged 13-33 years and 90% in patients aged 33-53 years. This study shows that the use of antibiotics in ARI patients at Koto Baru Health Center generally complies with therapeutic guidelines, especially in terms of the route of administration. However, there are some discrepancies in the frequency and rationality of antibiotic use that need to be addressed. Continuous education and training for medical personnel are necessary to improve the appropriateness of antibiotic use and reduce the risk of resistance